Estrategias metodológicas para el proceso de enseñanza aprendizaje de números reales en estudiantes de noveno año de Educación General Básica - Flores Encalada, Julissa Alexandra (2023)
Considering that the area of mathematics is where fewer methodological strategies are applied by teachers, which is reflected in students' school performance, leaves much to be desired. This research aims to determine and characterize the methodological strategies for the teaching-learning process of real numbers in ninth-year students of Basic General Education. Methodologically, it had a qualitative, documentary, and descriptive approach. The bibliographic review method was used to obtain information through logs and content sheets. Also, timelines were used to process the data. Following the results obtained, appropriate methodological strategies were determined for the teaching-learning process of real numbers, which were: game, brainstorming, and didactic material; from which it is concluded that they are valuable strategies to strengthen the abilities skills, attitudes, critical, reflective and reasoning capacities of the students so that they achieve meaningful learning. Keywords: methodological strategies, teaching-learning process, real numbers.